HUBUNGAN DEBITUR DENGAN KERIDITUR MELAKUKAN UTANG-PIUTANG DENGAN JAMINAN HAK MILIK ORANG LAIN - Danang Permadi; Imam Mahmudi (Institut Agama Islam Hasanuddin Pare, 2024)
In the reality of implementing credit agreements, it is often found that debtors use collateral in the name of the right holder, not themselves, in this case often referred to as a third party. The involvement of a third party in this credit agreement can be interpreted as meaning that the third party can cover the repayment of the credit by the Debtor, as explained in Article 1820 of the Civil Code which explains that guarantee is an agreement in which a third party, for the benefit of the debtor, binds himself to fulfill the obligation of the debtor. when this person himself does not fulfill it. It would be different if in practice the creditor claimed to be the person who plays a role in collecting funds from the public. By providing a form of loan that is based only on a written agreement. So even if in practice it continues like that, there will be a lot of losses, namely from the customer's side. Or even in the case of debts, creditors provide loans to debtors with large interest, which is paid weekly, not monthly, based on the loan amount given. So this violates Law No. 7 of 1992 concerning banking. If a creditor commits an act of default, there are several legal steps that can be taken, including making and sending a summons. A summons is a warning or warning given by the debtor to the creditor to immediately pay off the debt. Then, if the summons or warning is not implemented by the creditor, the debtor can take other legal action, namely filing a lawsuit for default at the District Court. Then, generally one of the legal steps that can be taken if a party is in default is to report the debtor to the police on charges of committing a criminal act of embezzlement and fraud.